Trigeminal Amyloidoma: A Report of Two Cases and Review of the Literature - Swanson, Amy; Giannini, Caterina; Link, Michael; Van Gompel, Jamie; Wald, John; McPhail, Ellen; Theis, Jason; Vaubel, Rachael (Journal of Neurological Surgery Part B: Skull Base, 2019)
Cerebral amyloidomas, characterized by localized amyloid deposits in the nervous system in the absence of systemic disease, are rare. These typically consist of immunoglobulin light chain (AL)-type, predominantly lambda. Trigeminal nerve involvement is exceptionally rare with only 21 previously reported cases, three with bilateral disease. We report two additional cases of amyloid localized to Meckel’s cave with secondary involvement of the trigeminal nerves bilaterally, with protein characterization by mass spectrometry. The patients, both females, 39 and 49-years-old, respectively, presented with the insidious onset of progressive trigeminal neuropathy, including pain and numbness with sensory loss, refractory to medical therapy. One patient experienced bilateral symptoms. Magnetic resonance imaging demonstrated abnormal thickening and contrast enhancement along Meckel’s cave bilaterally in both cases. The clinical differential diagnosis included benign neoplasms and inflammatory disorders. At the time of biopsy, the trigeminal nerve was noted to be enlarged and multinodular in one case and associated with abnormal soft tan tissue in the other case. Microscopically, the nerve biopsies showed extensive Congo red-positive amyloid deposits. Liquid chromatography tandem mass spectrometry demonstrated that the amyloid was of (AL)-type in both cases (AL [kappa] in one case and AL [lambda] in the other). After extensive evaluation, there was no evidence of systemic involvement. Both patients received localized radiotherapy for their refractory symptoms. One patient has stable symptomatology and imaging. No follow-up is available for the other patient.
Keywords: amyloidoma; trigeminal nerve; gasserian ganglion; cerebral amyloidoma